Effects of Calliandra Portoricensis Extracts on the Haematological Indices of Wistar Rats Challenged With Venom of Echis Ocellatus - Onyeama HP, Ebong PE, Eteng MU, Igile GO, Ibekwe HA, Atangwho IJ (Journal of Applied Pharmaceutical Science)
Effect of whole ethanolic and selective solvent extracts of C. portoricensis plant was carried out in wistar rats to ascertain their efficacy in ameliorating or attenuating the haemotoxicity of venom of carpet viper. A total of 30 wistar rats were used, divided into 6 rats per group of control, venom, venom/flavonoid-rich, venom/polyphenol-rich and venom/whole ethanolic extracts. The control was given nothing while the other groups were given 200μg venom/rat and 0.5 ml 100mg/100g body weight (b.w.) of rat as “anti-dote” concentration. This “antidote” was given intramuscularly 4-6 hours after the administration of the venom. The result obtained showed significant increase (P
Keywords: Calliandra portoricensis,Venom,Blood,Haemotoxin,Extract.